ANALISIS PENERAPAN PMK NO.136/PMK.03/2012 TENTANG PENUNJUKAN BUMN SEBAGAI WAPU PPN (Studi Pada PT. Pertamina Geothermal Energi Area Kamojang) - Kamalah Saadah; Norma Etika Wati (Jurnal Riset Akuntansi Politala, 2020)
This study aims to determine the description and analysis of the application of PMK No.136 / PMK.03 / 2012 which includes payment, deposit and reporting procedures for Value Added Tax at PT Pertamina Geothermal Energy (PGE) Kamojang Area. The method used in this research is descriptive qualitative method with data collection techniques by observation, interview and documentation. Data sources used in this study are primary and secondary data. This study produces a description that the obligations of PT PGE Kamojang Area as a Value Added Tax Taxpayer have been carried out properly in accordance with PMK No.136 / PMK.03 / 2012, but at the time of its implementation found errors from partner companies which resulted in delays. Further impacts will lead to the imposition of administrative fines for both parties. This research is expected to contribute input regarding Value Added Tax for PT PGE Kamojang Area to become a more orderly company in tax administration. The observations that have been made show that there are some discrepancies in the implementation of the Value Added Tax payment procedure. As a result, if it is not met, there will be sanctions for the delay in depositing and reporting the tax.